The Influence of Respondent Characteristics on Control Beliefs and Consumption Intentions of Processed Fish Products - Anindya Septisuwendani; Ujang Sumarwan; Mimin Aminah (Ridwan Institute, 2023)
Fish plays a crucial role as a source of animal protein, providing various health benefits to humans, such as heart health, nerve function, and brain health. Furthermore, global aquaculture production has been on the rise, with Indonesia ranking as the world's second-largest fish producer. However, the consumption of fish remains relatively low. The diversification of processed fish products may serve as a solution to address the issue of low fish consumption, with the hope of increasing the intention to consume processed fish products. This study aims to examine the influence of respondent characteristics on control beliefs and the intention to consume processed fish products. The research employs descriptive analysis and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The findings of the study reveal that respondent characteristics significantly impact control beliefs. However, respondent characteristics do not significantly influence the intention to consume. Additionally, control beliefs significantly influence the intention to consume processed fish products.